The application of open FOAM in modelling flow for vegetated channel - Muhammad Azizol Mohd Yusof,; Suraya Sharil,; Wan Hanna Melini Wan Mohtar,; Azam Che Idris,; Anuar Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Vegetation plays an important role in the hydrodynamic behaviour of an open channel flow. This study attempted to investigate the flow characteristics of an emergent vegetated channel using Open-source Operations and Manipulation (OpenFOAM). InterFoam is an OpenFOAM solver used to model this simulation. It is one of the methods available to model free-flow surface flow. Results for flow velocity profile can be generated using ParaView software. This study used a constant inlet velocity of 0.0417 m/s. There are two sets of models including model L8 with a solid volume fraction (SVF) of 8% using 9 rigid dowels, and model 4S with SVF of 4% using 17 dowels within a 1.2 m2 study area. Dowels in L8 are arranged in linear formation compared to the 4S model in a staggered arrangement. The study found that in model 4S, the stem-scale vortices are developed individually after each dowel due to sparse staggered vegetation. Meanwhile, model 8L suggests oppositely the vortex is cramped from the closeness of the dowels. The shear layer is formed as the flow enters the vegetation patch at upstream and the instability causes the shear layer vortices between inside and outside the vegetation region. Both models agreed that as the flow moves downstream the vortices are greater and make the streamwise velocity region become slower. The vertical velocity profile acknowledges the shear layer patch-scale vortices have a greater influence on the flow of both models. The magnitude of turbulence intensity in lateral directions is bigger in model 4S than in model 8L. The influence of vortices shed by upstream cylinders has an increasing impact on the irregular shedding behaviour of downstream cylinders as plant density increases. In general, the TKE values of the Model 4S are higher than those of the Model 8L. Regardless of the solid volume percentage difference, the vegetation pattern between linear and staggered has an effect on the flow. Computational Fluid Dynamic (CFD) is indeed capable to solve complex hydrodynamic characteristic.